Histological correlation of pipelle endometrial sampling with dilatation and curettage in abnormal uterine bleeding - Rachamallu, Lavanya; V, Bhavani; Byna, Prasanna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The current study was aimed to compare histopathological findings of endometrial aspiration biopsy by pipelle with endometrial biopsy obtained by dilatation and curettage. Methods: 82 women attending to gynaec OPD with complaint of AUB were selected as cases. First pipelle aspiration biopsy was done was before cervical dilatation and followed by D&C. Histopathology report of pipelle sample was compared with D&C sample. Results: There In the present study, menorrhagia was the most common bleeding pattern 43 (52.4%). In pipelle aspiration biopsy group, endometrial hyperplasia was reported in 42.6% of patients, secretory endometrium in 14.6% of patients, proliferative endometrium in 32.9 % of patients, atrophic endometrium in 6 % of patients and malignancy in 3.6 % of patients. In D&C group, 39 (47.5%) of patients had endometrial hyperplasia followed by proliferative endometrium in 24 (29.3%) of patients, secretory endometrium in 14.6 % of patients, atrophic endometrium in 4.8% of patients and malignancy in 3.6 % of patients. In D&C group, 39 patients had hyperplasia. Among them, 24 patients (61.5%) had simple hyperplasia, 11 patients (28.2%) had complex hyperplasia, 4 patients (10.2%) had atypical hyperplasia. In pipelle aspiration biopsy group, 35 patients had endometrial hyperplasia. Among them, 20 patients (57.1%) had simple hyperplasia, 11 patients (31.4%) had complex hyperplasia, 4 patients (11.4%) had atypical hyperplasia. Out of 82 cases, D & C diagnosed 46 cases as abnormal endometrium and pipelle aspiration diagnosed only 43 as abnormal endometrium. Regarding abnormal endometrium, there was a correlation in pipelle aspiration group and D&C group. Both show substantial agreement between the studies. Pipelle aspiration also has high sensitivity and negative predictive value of 93.47% and 92.3% respectively in diagnosing abnormal endometrium. In 46 patients who had endometrial pathology, pipelle aspiration biopsy diagnosed correctly in 42 patients. 4 cases of hyperplasia were wrongly diagnosed as proliferative endometrium in 3 cases, and in 1case as atrophic endometrium. Pipelle sampling has diagnosed all cases of malignancy, atrophy and secretory endometrium correctly. Pipelle aspiration also has high sensitivity and negative predictive value of 89.7% and 91.4% respectively in diagnosing hyperplastic endometrium. Conclusions: Hence pipelle aspiration biopsy is an alternative to traditional D& C in diagnosing endometrial pathology which is safer and quick.